Determination of Markers of Successful Implementation of Mental Health Apps for Young People: Systematic Review - Holly Alice Bear; Lara Ayala Nunes; John DeJesus; Shaun Liverpool; Bettina Moltrecht; Lakshmi Neelakantan; Elinor Harriss; Edward Watkins; Mina Fazel (JMIR Publications, 2022)
BackgroundSmartphone apps have the potential to address some of the current issues facing service provision for young people's mental health by improving the scalability of evidence-based mental health interventions. However, very few apps have been successfully implemented, and consensus on implementation measurement is lacking. ObjectiveThis review aims to determine the proportion of evidence-based mental health and well-being apps that have been successfully adopted and sustained in real-world settings. A secondary aim is to establish if key implementation determinants such as coproduction, acceptability, feasibility, appropriateness, and engagement contribute toward successful implementation and longevity. MethodsFollowing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, an electronic search of 5 databases in 2021 yielded 18,660 results. After full-text screening, 34 articles met the full eligibility criteria, providing data on 29 smartphone apps studied with individuals aged 15 to 25 years. ResultsOf 34 studies, only 10 (29%) studies were identified that were evaluating the effectiveness of 8 existing, commercially available mental health apps, and the remaining 24 (71%) studies reported the development and evaluation of 21 newly developed apps, of which 43% (9/21) were available, commercially or otherwise (eg, in mental health services), at the time of enquiry. Most studies addressed some implementation components including adoption, acceptability, appropriateness, feasibility, and engagement. Factors including high cost, funding constraints, and lengthy research processes impeded implementation. ConclusionsWithout addressing common implementation drivers, there is considerable redundancy in the translation of mobile mental health research findings into practice. Studies should embed implementation strategies from the outset of the planned research, build collaborations with partners already working in the field (academic and commercial) to capitalize on existing interventions and platforms, and modify and evaluate them for local contexts or target problems and populations. Trial RegistrationPROSPERO CRD42021224365; https://tinyurl.com/4umpn85f